2007
DOI: 10.1002/pssc.200675833
|View full text |Cite
|
Sign up to set email alerts
|

Positron diffusion in the liquid metal phase

Abstract: We have analyzed the positron diffusion length date in the liquid phase of In metal from the view point of the restoration of the spontaneously broken density around the positron. 1 Introduction The study of the dynamics of charged particles in liquids is significant not only for fundamental science but also for the chemical reactions in fluids. In order to understand the dynamics of charged particles in the liquid phase, we need to study the short-range structures of their fluctuations in liquids. Since fluct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…Open circles and solid circles correspond to experimental data points of In and Pb metals [15]. A dotted line is fitted one [23]. A solid line (the present work) is fitted one by using eq.…”
Section: The Hedgehog-like Density Fluctuation and The Positron Diffumentioning
confidence: 94%
See 2 more Smart Citations
“…Open circles and solid circles correspond to experimental data points of In and Pb metals [15]. A dotted line is fitted one [23]. A solid line (the present work) is fitted one by using eq.…”
Section: The Hedgehog-like Density Fluctuation and The Positron Diffumentioning
confidence: 94%
“…Kanazawa [16][17][18][19][20] has introduced the effective Lagrangian in the gauge-invariant formula with spontaneous symmetry breaking for liquids and glasses, and has discussed the origin of the boson peak, the glass transition, and the viscosity of the supercooled liquids. Kanazawa and coworkers [21][22][23][24] proposed a qualitative explanation for the increase of the positron diffusion length L + with temperature in the liquid phase, by using the theoretical formula, which is based on the gaugeinvariant effective Lagrangian with spontaneously broken density (the hedgehog like fluctuation) and the massive internal gauge fields. In addition Kanazawa et al [28] have suggested one origin of the attractive interaction between like ion pairs in liquids, extending the theoretical formula [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3. [13,14] A solid line is proportional to ~T1/4 . This relation is derived from "Polaronic" e + state explain experimental data well, as stressed by Seeger [15].…”
Section: The Spontaneously Broken Density With Internal Yang-mills Fi...mentioning
confidence: 99%